Joblessness, taxable income and regional divergence over time. Issue 3 (September 2014) - Corliss, Michael; Lewis, Phil
<x xml:space="preserve">Abstract</x> The debate over regional inequality and economic growth is ongoing. Previous research has shown that economic growth reduces regional disparity in the unemployment rate and increases regional disparity in income as measured by Census data. This paper examines the jobless rate and income from taxation data to further explore the effect economic growth has had upon regional inequalities. Here, we find while economic growth acts to significantly reduce jobless rates, the differences between statistical local areas is much more stubborn particularly for remote regions. Additionally, we show a much stronger link between economic growth and regional divergence in market income, with changes in economic growth impacting mostly upon statistical local areas with higher median incomes located in capital cities and remote regions.